Witamin D in children population - benefits and threats - Wójcik-Grudzień, Justyna; Ozga-Stachurska, Alicja; Pawłowska, Paulina; Rozenbajgier, Martyna (Journal of Education, Health and Sport, 2022)
Introduction Nowadays, it has become fashionable to use dietary supplements containing large doses of vitamin D available without a prescription. In the case of children, dietary supplementation with a properly selected dose of vitamin D is extremely important and brings many benefits, of which it is important to prevent rickets in the pediatric population, attention is also drawn to its toxicity and consequences in the event of an overdose of vitamin D preparations, to which infants and young children are most exposed, examples of risks are hypercalcemia, hypercalciuria and nephrocalcinosis. The aim of the study Showing the benefits and dangers of vitamin D supplementation. Material and methods The research was conducted using PubMed articles and on: vitamin D supplementation in children, vitamin D overdose, vitamin D deficiency. Description of the state of knowledge Vitamin D is the generic name for ergocalciferol and cholecalciferol that we can find in foods, however, food and supplementation are not its only sources, it should be borne in mind that it is possible to synthesize vitamin D in the skin after exposure to ultraviolet reproduction (UV-B). The concentration of 25(OH)D in childhood serum is influenced by the amount and frequency of vitamin D consumed, sun exposure, body weight and body fat levels. The main risk of vitamin D deficiency in children is rickets and defromation of the osteoarticular system and metabolic disorders, and long-term use of its high doses can lead to hypercalcemia and nephrocalcinosis. Summary It is very important to educate parents about the importance of vitamin D supplementation in a dose properly selected for the newborn along with an explanation of the possible consequences of deficiency, as well as overdose.